From disparity to inclusivity: Narrative review of strategies in medical education to bridge gender inequality - Han Ting Jillian Yeo; Dujeepa D. Samarasekera; Shuh Shing Lee (The Asia Pacific Scholar)
Introduction: Despite significant efforts to address gender equality in medical education, the issue persists. The narrative review aimed to address the research question: What are the strategies implemented to address issues of gender inequality in medical education and what were their outcomes? Methods: Seven major electronic databases of CINAHL, Embase, ERIC, PsyInfo, PubMed, SCOPUS and Web of Science were reviewed. Search phrases used were (Medical education) AND (Gender equality) OR (Gender bias) OR (Gender diversity) OR (Gender discrimination). Original research articles were included, together with systematic reviews with outcomes reporting on strategies to address gender equality. Results: Articles unrelated to medical education (e.g. allied health and nursing education) and non-English articles were excluded from the study. A total of 1248 articles were identified, and 23 articles met the inclusion criteria. Training programs (n=14; 60.8%) for medical students and faculty have successfully increased awareness on the issues of gender equality and boost confidence in handling cases on gender inequality, yet implicit bias remains with leadership continuing to be associated more strongly with males. Conclusion: Leadership bodies in Institutions of Higher Education and policymakers would be in an ideal position to address these issues through shaping policies and provision of training for hiring bodies and faculty.